Factors influencing insulin initiation in primary care facilities in Cape Town, South Africa - Tasunungurwa T. Mathose; Robert Mash (South African Family Practice)
Background: Type 2 diabetes (T2DM) is a leading cause of mortality in South Africa and resistance to the use of insulin is common. This study aimed to explore factors that influence the initiation of insulin in patients with T2DM in primary care facilities in Cape Town, South Africa.